EFFECT OF NIGELLA SATIVA EXTRACTS IN LIVER CELL OF RATTUS NORVEGICUS INDUCED BY PIROXICAM - Kurniasari, Septiana (Indonesian Physical Review, 2021)
Piroxicam has the potential to cause side effects, especially in the liver, so that it can causes cell damage and impair the function and work of the liver organs. One way to minimize liver cell damage is by giving black cumin (Nigella sativa). This study aims to analyze the effect of black cumin (Nigella sativa) extract on the level of liver cell damage in rats (Rattus norvegicus) induced by Piroxicam. This study used 80 male rats and divided into 3 groups, namely negative control (K-), Piroxicam non-extract (P-) and Piroxicam plus extract (P +). Black cumin extract is given orally at a dose of 2 gr/kgBW; 3 gr/kgBW; 4 gr/kgBW; 5 gr/kgBW and 6 gr/kgBW, while the Piroxicam dosage given is 1 g/kgBW and 3 g/kgBW. The liver cell damage was done by observing the microscopic image. The results showed that the more doses of Piroxicam were given, the higher the level of cell damage. Along with increasing the dose of black cumin extract, the cell damage is reduced.